Dark Witch - Roberts, Nora. (New York Berkley Books, 2013)
An American searches for her Irish ancestors to learn more about her powers and break an ancient curse.
Iona Sheehan has just taken the biggest gamble of her life. Leaving her job, her home and her family in Baltimore, she has come to Ireland in search of adventure -- and answers. Iona is excited to meet her cousins, Connor and Branna O'Dwyer, for the first time. And when she lands a job at the local riding school she finds herself drawn against her will to its owner -- the hot-tempered but charismatic Boyle McGrath. Connor, Branna and Iona have all inherited a powerful but dangerous gift from an ancestor known as the Dark Witch. And they are about to discover that some old legends can return to haunt the present...
Includes an excerpt from the two-hundredth novel by Nora Roberts, "The witness."
107954
Keywords: Americans -- Ireland -- Fiction; Man-woman relationships; Magic; .; Ireland; Romance fiction, English; .; Fantasy fiction; Love stories